Solutions and consequences of synchronous remote teaching and types of asynchronous communication - More Valencia, Rubén Alexander; Tume Ruiz, Juan Manuel; Rangel Vega, Antia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Sense of belonging and commitment evidenced in direct or synchronous communication messages were the basis of relationships between teachers and students in a difficult situation caused by the pandemic. Regarding the teaching environment, students felt responsibility and academic overload, with little time to finish homework, high levels of effort and dedication to get good grades, besides they were affected by the distractions generated by social networks, chats, and video games. Students in this research self-assessed consequences and solutions to emotional problems by academic stress, where considered positive aspects by complying with an action and organization plan. They developed the capacity for asynchronous communication in groups. It is necessary that the academic actors do not forget that emotions and attitudes were affected, planning for synchronous and asynchronous types of communication for activities and homework, as well as self-control that allowed solutions to students.